Learning through observing peers in practice. Issue 4 (2nd April 2016) - Tenenberg, Josh
Abstract : Learning through peer observation in higher education is most frequently investigated from the perspective of the teacher who is observed. What is under-examined is how learning arises for the observer by watching a peer in practice. This paper provides insight into this question through an interpretive-phenomenological analysis of a case study of an observer, elicited from a semi-structured interview following a peer observation. A three-part model of change resulting from observation is hypothesized, and two important social conditions unique to this peer observation are identified that appear to have causal import for learning. This paper adds to the increasing evidence about the value of peer observation for learning and development for the observer.